Taxonomy of the genus Chlamisus Rafinesque (Coleoptera: Chrysomelidae) from China with description of three new species - Su, Liang; Zhou, Hong-Zhang (Zootaxa, 2017)
This study is focused on the Chinese fauna of the leaf beetle genus Chlamisus Rafinesque, 1815 (Coleoptera: Chrysomelidae) and three new species are described, namely C. corollinotatus sp. nov. from Guangxi, and C. lycocephalus sp. nov. and C. varipennatus sp. nov. from Yunnan. The number of the Chinese Chlamisus is thus increased to 66. Twenty-five species are redescribed with the emphasis mainly on the genital morphological characters that are observed and reported for the first time for most species of the genus from China. Color plates and line drawings of general habitus and other detailed structures are also provided. Chinese fauna of the genus is keyed to species. Type specimens of the new species and other materials included in this study are deposited in the Institute of Zoology, the Chinese Academy of Sciences, Beijing.